1998
DOI: 10.1023/a:1005075112393
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: A study to determine the secretion of Mycobacterium spp. in milk from indigenous cattle was carried out in pastoral cattle reared in the Southern Highlands to Tanzania. The study was aimed at elucidating the dangers associated with milk-borne zoonoses in a society where milk is normally consumed raw. Out of 805 milk samples, 31 (3.9%) were positive for mycobacteria. There was a preponderance of atypical mycobacteria (87%) whereas only two isolates (6.5%) were confirmed as M. bovis. Atypical mycobacteria includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(30 citation statements)
references
References 6 publications
1
27
2
Order By: Relevance
“…The prevalence of M. bovis-infection in cattle demonstrated in the present study is in the same range as demonstrated previously for this region of Tanzania (Shirima et al 2003). The proportion of milk samples resulting in a positive mycobacterial culture (19%) was higher than the proportion of 4% previously reported by Kazwala et al (1998). This is probably because in our study only milk samples from SCITT-reacting animals were taken whereas Kazwala et al (1998) collected milk samples after SCITT-testing from all animals regardless of their SCITT status.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The prevalence of M. bovis-infection in cattle demonstrated in the present study is in the same range as demonstrated previously for this region of Tanzania (Shirima et al 2003). The proportion of milk samples resulting in a positive mycobacterial culture (19%) was higher than the proportion of 4% previously reported by Kazwala et al (1998). This is probably because in our study only milk samples from SCITT-reacting animals were taken whereas Kazwala et al (1998) collected milk samples after SCITT-testing from all animals regardless of their SCITT status.…”
Section: Discussionsupporting
confidence: 87%
“…The proportion of milk samples resulting in a positive mycobacterial culture (19%) was higher than the proportion of 4% previously reported by Kazwala et al (1998). This is probably because in our study only milk samples from SCITT-reacting animals were taken whereas Kazwala et al (1998) collected milk samples after SCITT-testing from all animals regardless of their SCITT status. All mycobacteria isolated in this study were atypical mycobacteria with limited or no pathogenicity.…”
Section: Discussioncontrasting
confidence: 62%
“…This was different from earlier reports, which associate raw milk consumption with extra pulmonary TB [32][34]. As indicated earlier, only 1% of the cows with TB excrete tubercle bacilli in their milk [35], which decreases probability of milk transmitting M. bovis to humans.…”
Section: Discussioncontrasting
confidence: 74%
“…In general, the program requires culling of reactor animals, standardized diagnostic tests and equipment (automatic antigen applicator and callipers), and training of veterinarians in diagnostic procedures 26 . In 2011, the Brazilian Normative Instruction (IN) 62 28 was established (replacing IN 51) standardizing procedures from production to the marketing of different types of milk in the country, with emphasis on the quality control of raw milk.…”
Section: Introductionmentioning
confidence: 99%